2005
DOI: 10.1007/s00464-005-0235-1
|View full text |Cite
|
Sign up to set email alerts
|

National analysis of in-hospital resource utilization in choledocholithiasis management using propensity scores

Abstract: Based on this PS analysis, CBDE incurs less THC, reduces LOS, and has less estimated costs for CDL compared to ERCP. Furthermore, CBDE appears to be dramatically underutilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 18 publications
1
79
0
2
Order By: Relevance
“…It is important also to note that, although the laparoscopic technique appears to be equivalent to ERCP and may be more cost effective 17,33 , it has not been widely accepted by the surgical community 17 . A recent survey of general surgeons practising in the USA showed that, although 30 (44 per cent) of 68 confirmed they could perform laparoscopic CBD exploration, only 15 (22 per cent) actually did so routinely 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important also to note that, although the laparoscopic technique appears to be equivalent to ERCP and may be more cost effective 17,33 , it has not been widely accepted by the surgical community 17 . A recent survey of general surgeons practising in the USA showed that, although 30 (44 per cent) of 68 confirmed they could perform laparoscopic CBD exploration, only 15 (22 per cent) actually did so routinely 5 .…”
Section: Discussionmentioning
confidence: 99%
“…With the development of accurate preoperative non-invasive CBD imaging based on magnetic resonance cholangiopancreatography, further complex preoperative algorithms were instituted 16 . Today, the laparoscopic management of choledocholithiasis is increasingly reported with the emergence of an argument to return to one-stage surgical management of choledocholithiasis 17 ; this has not been widely accepted by general surgeons 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies of laparoscopic management of CBDS that included more than 200 patients report success rates ranging from 88% to 97% (mean 92%) [3,4,9], similar to ES success rates, which range from 81% to 100% (mean 91%), but the clearance of CBDS after ES is obtained in 17-35% of cases after two to five attempts [5][6][7]11], while laparoscopic treatment of CBDS is a one-stage procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Several reports have demonstrated the feasibility, safety, efficiency and cost-effectiveness of laparoscopic techniques [1][2][3][4]. Prospective studies of laparoscopic management of CBD stones (CBDS) that included more than 200 patients report success rates ranging from 88% to 97% (mean 92%) [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation